Team-efficacy dispersion pattern and team creativity - FRANC, Michal (Institutional Knowledge at Singapore Management University, 2017)
Present study compared the effect of two team efficacy (i.e., team members’ belief that the team can successfully perform a specific task) dispersion patterns in their effect on team creativity. Two dispersion patterns were manipulated such that the first one consisted of team members sharing an average level of team efficacy belief (i.e., shared team efficacy pattern), while the second dispersion pattern consisted of a majority of team members sharing a below average level of team efficacy belief and one minority member with relatively higher team efficacy belief (i.e., minority member team efficacy pattern) (DeRue, Hollenbeck, Ilgen, & Feltz, 2010). Using motivated information processing in group model (De Dreu, Nijstad, & van Knippenberg, 2008), it was predicted that individuals who were assigned to minority members with a high team efficacy belief would engage in more discussion facilitating behaviors, which would induce higher information elaboration on the team level and consequently lead to higher team creativity. A laboratory team study (257 participants in 71 teams) was used to manipulate team efficacy patterns and measure their effect on team processes and team creativity during a brainstorming session. The results showed that minority members expressed significantly more ideas when they perceived their efforts as indispensable for team effort. Theoretical implications of these findings for conceptualizations of team efficacy on team level and for motivated information processing in group model were discussed.